ELLO FLOOD ATTACK AND WAYS OF PROTECTION IN WIRELESS SENSOR NETWORKS (INTERNATIONAL SCIENCE REVIEWS. NATURAL SCIENCES AND TECHNOLOGIES SERIES, 2024)
Annotation. There are many vulnerabilities to attack in wireless sensor networks. Wireless sensor network has become an important application of the paradigm of special networks, for example, for monitoring the physical environment. These sensor networks have limitations on system resources such as battery power, communication range, and processing capabilities. Low computing power and wireless connectivity make these networks vulnerable to various types of network attacks. One of them is the hello flood attack, in which an attacker who is not a legal host on the network can send a hello request to any legitimate host and violate the security of WSN. The current solutions for these types of attacks are mainly cryptographic, which suffer from high computational complexity. Therefore, they are less suitable for wireless sensor networks.